Itraconazole prophylaxis for invasive Aspergillus infection in lung transplantation. Issue 2 (5th March 2014) - Kato, K.; Nagao, M.; Nakano, S.; Yunoki, T.; Hotta, G.; Yamamoto, M.; Matsumura, Y.; Ito, Y.; Takakura, S.; Chen, F.; Bando, T.; Matsuda, Y.; et al.
Abstract Invasive Aspergillus infection (IA) is a significant cause of morbidity in lung transplantation (LT). However, its optimal prophylaxis is unclear. We routinely administer itraconazole (ITCZ) prophylaxis to all patients undergoing LT. In this study, we retrospectively evaluated the duration of prophylaxis and risk factors of IA. Among 30 adult patients who underwent LT, 5 patients developed IA. All patients with IA stopped ITCZ treatment within 1 year. At least 1 year of ITCZ prophylaxis is essential for the prevention of IA. Cytomegalovirus infection, renal replacement therapy, and tracheotomy were risk factors for IA.